2021
DOI: 10.3390/cryst11070791
|View full text |Cite
|
Sign up to set email alerts
|

Electric Double Layer Doping of Charge-Ordered Insulators α-(BEDT-TTF)2I3 and α-(BETS)2I3

Abstract: Field-effect transistors based on strongly correlated insulators are an excellent platform for studying the electronic phase transition and simultaneously developing phase transition transistors. Molecular conductors are suitable for phase transition transistors owing to the high tunability of the electronic states. Molecular Mott transistors show field-induced phase transitions including superconducting transitions. However, their application to charge-ordered insulators is limited. In this study, we fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Researchers have demonstrated gate-induced insulator-to-metal transitions (IMTs), superconductivity, or ferromagnetism in EDLTs based on metal oxides, metal sulfides, and 2D materials such as graphene, , tellurene, , and MoS 2 . EDLTs have also been employed to examine charge ordering phenomena, Mott physics, and very recently an IMT in organic conductors. Here we report EDLT measurements on single crystals of the well-known organic semiconductor C 60 , Figure a. C 60 is an intriguing choice for EDLT transport measurements as it is known to undergo a chemical doping-induced IMT and a metal-to-superconductor transition at 3 electrons/molecule. Because C 60 is a large molecule (radius r C60 = 0.35 nm), the molecular density of the (111) close-packed plane of face centered cubic (FCC) C 60 crystals is relatively low at 1.1 × 10 14 cm –2 , which is comparable to the achievable 2D charge densities in EDLTs.…”
mentioning
confidence: 94%
“…Researchers have demonstrated gate-induced insulator-to-metal transitions (IMTs), superconductivity, or ferromagnetism in EDLTs based on metal oxides, metal sulfides, and 2D materials such as graphene, , tellurene, , and MoS 2 . EDLTs have also been employed to examine charge ordering phenomena, Mott physics, and very recently an IMT in organic conductors. Here we report EDLT measurements on single crystals of the well-known organic semiconductor C 60 , Figure a. C 60 is an intriguing choice for EDLT transport measurements as it is known to undergo a chemical doping-induced IMT and a metal-to-superconductor transition at 3 electrons/molecule. Because C 60 is a large molecule (radius r C60 = 0.35 nm), the molecular density of the (111) close-packed plane of face centered cubic (FCC) C 60 crystals is relatively low at 1.1 × 10 14 cm –2 , which is comparable to the achievable 2D charge densities in EDLTs.…”
mentioning
confidence: 94%
“…• Kawasugi et al reported doping effects using field-effect transistors consisting of electric double layers of charge-ordered insulators, α-(BEDT-TTF) 2 I 3 , and α-(BETS) 2 I 3 [24].…”
mentioning
confidence: 99%